Curative resection of advanced esophageal cancer with metachronous stage IV breast cancer: A case report. (2018) - Gokon, Yusuke; Sakurai, Tadashi; Fujishima, Fumiyoshi; Taniyama, Yusuke; Heishi, Takahiro; Okamoto, Hiroshi; Maruyama, Shota; Ishida, Hirotaka; Onodera, Yu; Sasano, Hironobu; Kamei, Takashi
Highlights: Our literature search revealed no curative surgery cases for esophageal cancer in patients with multiple primary cancers with distant metastasis. We report a case of esophageal cancer with metachronous breast cancer involving liver and mediastinal lymph node metastasis and cancerous peritonitis. Curative resection of esophageal cancer can be considered when the prognosis of the additional cancer is not poor. Abstract: Introduction: Recent studies have shown the safety and efficacy of curative resection of esophageal cancer with multiple primary cancers. However, our literature search revealed no curative surgery cases for esophageal cancer in patients with multiple primary cancers with distant metastasis. Case presentation: A 75-year-old woman visited our hospital with dysphagia. She had a history of breast cancer with multiple bone metastasis. Esophagogastroduodenoscopy revealed a circumferential mass in the upper intrathoracic esophagus. Histopathological examination of the biopsy showed squamous cell carcinoma. Other imaging findings revealed multiple nodules in the liver. The nodules were thought to have originated from the breast, but metastasis of esophageal cancer was considered a possibility. Intraoperative frozen sections of the liver and peritoneal nodules showed adenocarcinoma. Thoracoscopic esophagectomy was then performed. Following surgery, the patient received fulvestrant therapy, followed by capecitabine therapy, and the liver tumors decreased in size. She is currently alive after 1.5 years of the surgery without local recurrence of esophageal cancer. Discussion: Although the patient had metastatic breast cancer, her relapse-free interval of 20 years and good response to hormone therapy for 15 years were favorable prognostic factors. Her life expectancy was estimated to be a few years and surgery was performed. Conclusion: Curative resection could be considered for patients with esophageal cancer who have an additional cancer with distant metastasis when the prognosis of the additional cancer is not poor.